1998
DOI: 10.1093/bja/81.5.727
|View full text |Cite
|
Sign up to set email alerts
|

Balanced pre-emptive analgesia: does it work? A double-blind, controlled study in bilaterally symmetrical oral surgery

Abstract: We studied 32 patients undergoing bilateral symmetrical lower third molar surgery under general anaesthesia to determine if the combined effects of pre-emptive local anaesthetic block using 0.5% bupivacaine, together with i.v. tenoxicam and alfentanil had any benefits over postoperative administration. Patients acted as their own controls and were allocated randomly to have surgery start on one side, the second side always being the pre-emptive side. Difference in pain intensity between the two sides was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
0
15
0
3
Order By: Relevance
“…The degree of difficulty of the procedure was evaluated using the following 4-grade scale presented by CAMPBELL et al 4 : (i) simple tooth extraction, (ii) bone removal or tooth division, (iii) bone removal and tooth division and (iv) the same as (iii) but very difficult. After surgery, the patients were discharged from the hospital with a prescription of loxoprofen tablets, 60 mg per tablet, for postoperative pain relief.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of difficulty of the procedure was evaluated using the following 4-grade scale presented by CAMPBELL et al 4 : (i) simple tooth extraction, (ii) bone removal or tooth division, (iii) bone removal and tooth division and (iv) the same as (iii) but very difficult. After surgery, the patients were discharged from the hospital with a prescription of loxoprofen tablets, 60 mg per tablet, for postoperative pain relief.…”
Section: Methodsmentioning
confidence: 99%
“…The pathophysiological mechanisms of such neuropathic pain have been elucidated 8,20 and a number of interventions have been attempted to prevent or reduce postoperative pain 2,4,13,14,23,24 . Non-steroidal anti-inflammatory drugs (NSAIDs) are one of the examples 2,4,13,14,23,24 , but are still controversial 2,3,13,14 .…”
mentioning
confidence: 99%
“…A number of editorials and reviews of this topic published at the time suggested the need for improved study designs in order to obtain more convincing results [18][19][20][21]. Many preemptive analgesia studies have been carried out since that time, incorporating the design improvements suggested (eg, effect proven [22][23][24][25][26][27][28][29][30][31]; no effect proven [32][33][34][35][36][37]). Although this has resulted in more success in proving an effect of preemptive analgesia for certain substances (notably opioids, local anesthetics, and NMDA-receptor antagonists), the effects demonstrated have remained clinically modest and of short duration.…”
Section: Sensory Change and The Concept Of Preemptive Analgesiamentioning
confidence: 99%
“…The same extraction technique was employed for all patients. The degree of difficulty of the procedure was evaluated using the following four-grade scale presented by Campbell et al [13]; (i) simple tooth extraction, (ii) bone removal or tooth division, (iii) bone removal and tooth division, and (iv) the same as (iii) but very difficult.…”
Section: Surgerymentioning
confidence: 99%